Fibrodysplasia ossificans progressiva in a 3-year-old female patient - Cecilia Moreira; Gabriel Dapueto; Gabriel Peluffo; Alejandra Vomero; Alejandra Tapié; Soledad Rodríguez; Victor Raggio; Rodrigo Suárez; Gustavo Giachetto; Loreley García (Permanyer, 2023)
Background: Fibrodysplasia ossificans progressiva (FOP) is a rare autosomal dominant disease affecting connective tissue, primarily caused by de novo mutations of the ACVR1 gene. FOP is a disease with congenital malformations of the toes and heterotopic ossification in characteristic patterns that progresses with flare-ups and remissions. Cumulative damage results in disability and, eventually, death. This report aimed to describe a case of FOP to highlight the importance of early diagnosis of this rare condition. Case report: We describe the case of a 3-year-old female diagnosed with congenital hallux valgus, who initially presented with soft tissue tumors, predominantly in the neck and chest, with partial remission. Multiple diagnostic tests were performed, including biopsies and magnetic resonance imaging, with nonspecific results. We observed ossification of the biceps brachii muscle during evolution. The molecular genetic study found a heterozygous ACVR1 gene mutation that confirmed FOP. Conclusions: Knowledge of this rare disease by pediatricians is critical for an early diagnosis and for avoiding unnecessary invasive procedures that may promote disease progression. In case of clinical suspicion, performing an early molecular study is suggested to detect ACVR1 gene mutations. The treatment of FOP is symptomatic and focused on maintaining physical function and family support.